Gouty tophi in the thoracic spinal canal with incomplete paraplegia: a case report - Zhao, Chunyu; Deng, Juncai; Ding, Jingzhe; Zhang, Kunpeng; Zhang, Jian (Frontiers in Surgery, 2025)
Gout manifesting in the spine is a relatively rare occurrence. Involvement of the lumbar spine is more common in cases of spinal gout, while reports of gouty tophi forming within the thoracic spinal canal are exceedingly rare. This article reports a case of incomplete paraplegia caused by gouty tophi in the thoracic spinal canal. The patient, a 56-year-old man, returned to normal after undergoing surgical treatment and was monitored for ten months postoperatively. This case highlights the importance of early diagnosis of spinal gout to prevent the progression of neurological symptoms. Surgical treatment for paraplegia caused by intraspinal tophi can yield favorable clinical outcomes. Increasing awareness of spinal gout and implementing effective uric acid management strategies are essential for preventing the severe consequences associated with this condition.